Production of hydroxyapatite (HAP) nanoparticles by direct precipitation - Syahirah Binti Ibrahim (School of Bioprocess Engineering, University Malaysia Perlis, 2017)
Hydroxyapatite (HAp) nanoparticles, (Ca10(PO4)6(OH)2) has been extensively used in biomedical field and drug delivery system. HAp nanoparticles were synthesized via direct precipitation method by varying different processing temperature, agitation speed and stirring time. Calcium nitrate tetrahydrate (Ca(Na3)2.4H2O) and ammonium dihydrogen phosphate (NH4H2PO4) were used as precursors and were dissolved in distilled water to form a cloudy suspension. The solution was mixed on the hot plate magnetic stirrer beaker followed by drying and filter process to obtain a white precipitated powder. Nano HAp powder has been studied at different process temperature which is 20 to 60 C, agitation speed from 200 to 600 rpm and stirring time at 15 minutes to 45 minutes. Response Surface Methodology (RSM) and Central Composite Design (CCD) was carried out by Design Expert Software (DOE) to obtain the smallest particles of HAp based on optimum condition. From the experimental result, the minimum crystallite size of HAp is 36.51 nm at 51.89 C process temperature, for 38.91 min and 500 rpm. Based on analysis of variance (ANOVA), stirring temperature and agitation speed was to be influential variable on crystallite size of HAp with volume of probability less than 0.05. The powder samples was analyzed to study the functional group, crystallinity morphology and hence confirmed the present of HAp nanoparticles in the powder samples. The characterization was evaluated by X-Ray diffraction (XRD), Fourier Transform Infrared (FT-IR) and Scanning Electron Microscopy (SEM).The result shows, the pure HAp was obtained at the highest peak of 31.8 at 25. FTIR confirmed the presence of hydroxyl (O-H), phosphate (P-O) and carbonate (C-O) functional group which indicated the HAp nanoparticles while the morphology of the HAp nanoparticles was identified as plate- like shape and appeared as agglomerates.